Data showing non-conventional HLA-B27 expression in axial joints and gut tissue from B27 transgenic rats, and in frozen and paraffin-fixed synovial SpA tissue - Rysnik, Oliwia (Data Brief, 2016)
Data is presented showing expression of non-conventional (NC) heavy chain forms of B27 in synovial tissues from SpA patients. Data is presented showing the expression patterns of NC-B27 in joint, gastrointestinal and lymphoid tissues from B27 transgenic (TG(1)) rats with M. tuberculosis-induced SpA. Expression of NC-B27 was determined by immunohistochemistry and flow cytometry using HC10 and HD6 antibodies. These data are the extension of the data presented and discussed in “Non-conventional forms of HLA-B27 are expressed in Spondyloarthritis joints and gut tissue” (O. Rysnik, K. McHugh, L. M. van Duivenvoorde, M. N. van Tok, G. Guggino, J. D. Taurog, S. Kollnberger, F. Ciccia, D. L. Baeten, P. Bowness, 2016) [1].